Desain dan Uji Kelayakan Modul IPS Berbasis Sejarah Lokal pada Materi Perjuangan Melawan Penjajah di Kabupaten Aceh Besar - Novita Hanum; Mukti Kanaya Sidiq; Maisyaroh Maisyaroh (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study designs and tests the feasibility of a local history-based Social Studies (IPS) module on anti-colonial struggles in Aceh Besar Regency. Using a Research and Development (R&D) approach, the module was developed through the Dick and Carey instructional design model adapted into a modified Borg and Gall procedure (problem identification, design-development, and dissemination). The study involved fifth-grade elementary students in Ingin Jaya Subdistrict, Aceh Besar, with trials conducted in four selected schools. Data were collected through expert validation (content, language, and presentation/design), practitioner assessments, student activity observation, and achievement tests. Data were analyzed using descriptive quantitative techniques with percentage and rating-scale interpretation. The module achieved high feasibility, indicated by expert validation results of 86% (language), 88% (content), and 98% (presentation), while practitioner scores ranged from 86% to 97%. The overall feasibility mean was 90.14%, confirming that the module is valid and suitable for classroom implementation.